2015
DOI: 10.1039/c5mt00133a
|View full text |Cite
|
Sign up to set email alerts
|

Methionine oxidation of amyloid peptides by peroxovanadium complexes: inhibition of fibril formation through a distinct mechanism

Abstract: Fibril formation of amyloid peptides is linked to a number of pathological states. The prion protein (PrP) and amyloid-β (Aβ) are two remarkable examples that are correlated with prion disorders and Alzheimer's disease, respectively. Metal complexes, such as those formed by platinum and ruthenium compounds, can act as inhibitors against peptide aggregation primarily through metal coordination. This study revealed the inhibitory effect of two peroxovanadium complexes, (NH4)[VO(O2)2(bipy)]·4H2O (1) and (NH4)[VO(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 67 publications
(82 reference statements)
0
24
0
Order By: Relevance
“…In addition, a number of groups have explored the use of discrete metal complexes for the diagnosis and treatment of AD 20. In terms of therapeutics, Pt,21 Ru,22 Ir,23 Co,10b,24 Re,25 Rh,26 Mn,27 and V28 complexes have been investigated for their ability to modify the aggregation of the Aβ peptide, and certain compounds have shown promising results in disease models. For example, an orally-available Pt( iv ) complex (Scheme 1) was shown to cross the blood–brain barrier (BBB), reduce plaque burden, and reduce Aβ peptide levels in a APP/Ps1 mouse model 29.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a number of groups have explored the use of discrete metal complexes for the diagnosis and treatment of AD 20. In terms of therapeutics, Pt,21 Ru,22 Ir,23 Co,10b,24 Re,25 Rh,26 Mn,27 and V28 complexes have been investigated for their ability to modify the aggregation of the Aβ peptide, and certain compounds have shown promising results in disease models. For example, an orally-available Pt( iv ) complex (Scheme 1) was shown to cross the blood–brain barrier (BBB), reduce plaque burden, and reduce Aβ peptide levels in a APP/Ps1 mouse model 29.…”
Section: Introductionmentioning
confidence: 99%
“…A number of Pt (Barnham et al, 2008;Sasaki et al, 2012;Collin et al, 2013;Streltsov et al, 2013), Ru (Valensin et al, 2010;Messori et al, 2013;Jones et al, 2015), Co (Suh et al, 2007;Heffern et al, 2014;Derrick et al, 2017), and V (He et al, 2015) metal complexes have shown promise in interacting with the Aβ peptide and modifying its aggregation. For example, a series of Pt(II) phenanthroline complexes (Chart 1) were shown to bind to the peptide, modulating the aggregation and the neurotoxicity of Aβ (Barnham et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Methionine oxidation is an important event. It plays roles in fibrillation of -amyloid peptide and -synuclein, and thus in Alzheimer's [45,46] and Parkinson's diseases [47,48]. Methionine sulfoxide is among the rare oxidized forms that can be repaired.…”
Section: Resultsmentioning
confidence: 99%